Материалы по питанию некоторых воробьиных птиц Памиро-Алая - Пекло, А.М. (Вестник зоологии, 1982)
On the baseof 156 samplesanalysis and fieldobservations, the feed and feeding behaviour during the nest period is described for Hirundosmithi, Terpsiphone paradisi leucogaster, Muscicapa striata ncumanni and M. ruficauda of Pamir-Alai mountain range.